Allogenic hematopoietic stem cell transplantation in pemphigus vulgaris: A single-center experience - Aruna V Vanikar; Hargovind L Trivedi; Rashmi D Patel; Kamal V Kanodia; Pranjal R Modi; Veena R Shah (Wolters Kluwer Medknow Publications, 2012)
Background: Pemphigus vulgaris (PV), an autoimmune disorder characterized by blistering skin/mucus membrane lesions, is mediated by desmoglein-3 autoantibodies. We carried out a prospective clinical trial of hematopoietic stem cell transplantation (HSCT) in thymus, bone marrow (BM) and periphery to reconstitute central and peripheral arms of self-tolerance. Materials and Methods: Eleven (M:F=5:6) patients with mean age 33.5 years and mean duration of disease 22.8 months, having painful pruritic blisters and ulcers resistant to corticosteroids, were treated with cytokine-stimulated allogeneic HSCT (mean dose: 21.8 Χ 10 8 cells/kg BW) from blood group-matched related donors. BM with mean CD34+ count 1.1% was inoculated into thymus, marrow and periphery, followed by two peripheral blood stem cell (PBSC) infusions. Results: Recovery began within 24 hours of HSCT and new lesions stopped after 6 months. No graft versus host disease (GvHD)/adverse effect was observed in any patient/donor. Over a mean follow-up of 8.02 years, all patients were well without recurrence/new lesions. Conclusion: Drug-resistant PV can be successfully and safely treated by allogeneic HSCT.